First Evidence of Microplastics in the Yolk and Embryos of Common Cuttlefish (Sepia officinalis) from the Central Adriatic Sea: Evaluation of Embryo and Hatchling Structural Integrity and Development - Giulia Chemello; Viola Faraoni; Valentina Notarstefano; Francesca Maradonna; Oliana Carnevali; Giorgia Gioacchini (Animals, 2022)
Once they reach the aquatic environment, microplastics (MPs) are accidentally ingested by aquatic biota, thus entering the food chain with possible negative effects. The present study investigated, for the first time, MP presence in cuttlefish (Sepia officinalis) eggs and their association with embryonic development. Cuttlefish eggs were sampled from four different sites along the Marche region (Senigallia, Ancona, Numana, and San Benedetto del Tronto). Embryo and hatchling biometric parameters were evaluated and the internal structural integrity was examined through histological analysis. MPs were detected and characterized in embryos and yolk samples. MPs were identified in all sites (size < 5 µm), however, their presence has not been associated with an impairment of either embryo or hatchling internal structures. Noteworthy, the highest number of MPs (in both yolk and embryo samples) were found in Numana (37% of the total amount), where the lowest hatchling size was observed. On the other hand, the highest embryo mantle length was associated with the lowest number of MPs detected (9%) in Ancona. Overall, only MP fragments and sphere types (74 and 26%, respectively) were observed, and the most frequent polymers were Polyvinyl chloride (52%), Polypropylene, and Cellulose acetate (15% both). Further studies are needed to assess the possible MP effects on the yolk quality and assimilation.